Trading Volume Levels and Stock Returns: Empirical Behavioral Analysis - Moatemri, Ouarda; El-Bori, Abdelfeteh (International Journal of Economics and Financial Issues, 2017)
The objective of this paper is to provide an empirical behavioral analysis of the relationship between the trading volume and the future evolution of stock returns. This subject has been examined empirically on the European financial market during 2000-2010. Our empiric findings suggest monotonous relationships between the trading volumes and the schemas of price evolution in terms of the continuity/reversal of prices that vary amongst the trading volume levels as well as amongst the winning and losing shares. Excess volume is thus more dependent on “momentum” profits for loser portfolios and on “contrarian” profits for winner portfolios. Keywords: Trading Volume Levels, Momentum Profits, Contrarian Profits, Behavioral Analysis and Loser/Winner Portfolios JEL Classifications: G12 G14